2007
DOI: 10.1128/aem.02218-06
|View full text |Cite
|
Sign up to set email alerts
|

Does the Antibacterial Activity of Silver Nanoparticles Depend on the Shape of the Nanoparticle? A Study of the Gram-Negative Bacterium Escherichia coli

Abstract: In this work we investigated the antibacterial properties of differently shaped silver nanoparticles against the gram-negative bacterium Escherichia coli, both in liquid systems and on agar plates. Energy-filtering transmission electron microscopy images revealed considerable changes in the cell membranes upon treatment, resulting in cell death. Truncated triangular silver nanoplates with a {111} lattice plane as the basal plane displayed the strongest biocidal action, compared with spherical and rod-shaped na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

103
2,192
6
61

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 3,705 publications
(2,473 citation statements)
references
References 41 publications
103
2,192
6
61
Order By: Relevance
“…As concentration of nanoparticles increased to MIC of the respective strains, no growth was observed in the flask. The bactericidal effect of nanoparticles is dependent on the concentration of nanoparticles and the initial bacterial concentration [24]. In this study, the initial bacterial concentration was almost constant at 10 3 -10 4 CFU ml À1 irrespective of nanoparticle concentration and microbial strain.…”
Section: Resultsmentioning
confidence: 56%
See 1 more Smart Citation
“…As concentration of nanoparticles increased to MIC of the respective strains, no growth was observed in the flask. The bactericidal effect of nanoparticles is dependent on the concentration of nanoparticles and the initial bacterial concentration [24]. In this study, the initial bacterial concentration was almost constant at 10 3 -10 4 CFU ml À1 irrespective of nanoparticle concentration and microbial strain.…”
Section: Resultsmentioning
confidence: 56%
“…Some of the silver nanoparticles also penetrate into the cells. It is reported that the bactericidal effect of silver nanoparticles decreases as the size increases and is also affected by the shape of the particles [23,24]. Although most studies have utilized spherical particles, truncated triangular shaped particles are reported to have greater bactericidal effect compared to that of spherical and rodshaped particles [24].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the requirement of the Ag NPs to dissolve and to release Ag + ions can contribute explaining the size and shape dependency of the nanoparticle action [62]. Most studies show indeed a size dependency of the antimicrobial activity of (quasi-spherical) nanoparticles, the smaller being the more active [63].…”
Section: Role Of Ag + Speciesmentioning
confidence: 99%
“…Nanoparticles present a higher surface area to volume ratio with decrease in the size of the particles. Specific surface area is relevant to catalytic activity and other related properties such as antimicrobial activity of AgNPs [3][4][5] . As the specific surface area of nanoparticles is increased, their biological effectiveness can also increase on the account of a rise in surface energy.…”
Section: Introductionmentioning
confidence: 99%